ADDRESSING HEALTH EQUITY IN RILEY COUNTY - Zavala, Alexis (My University, 2018)
This report details an applied learning experience completed with the Flint Hills Wellness Coalition under the supervision of the Julie Hettinger, Health Educator at the Riley County Health Department and Past-Chair of the Flint Hills Wellness Coalition. The scope of work includes time spent as the Flint Hills Wellness Coalition intern. As an intern (formally known as the Coalition Liaison), the focus was on capacity building, communication, and health equity.
Keywords: Flint Hills Wellenss Coalition; health equity; Riley County Kansas